20 students gain knowledge about coral reefs and ecosystem - Siti Rabiatull Aisha, Idris (2020)
Kuantan, 21 August 2020 - For the first time, the Co-curriculum Centre, Student Affairs and Alumni Department, Universiti Malaysia Pahang (UMP) organised an Education-Based Community Service Programme: Coral Reefs and Its Impact on the Ecosystem in collaboration with Simply Scooba Industries.